Development of a Total War Strategy to Face Cyber Threats in Aviation Systems: a Case Study of Asean Regional Strategic Environment and its Implications for Aviation Security - Anggreini, Monika; Priyanto, Priyanto; Sulistyanto, Sulistyanto; Hendra, Afrizal; Suryo, Almuchalif (CV. Publikasi Indonesia, 2025)
This research aims to analyze the implementation of aviation security in the face of cyber threats and formulate the best strategies to strengthen national digital defense in the perspective of the Universal War Strategy. The background of this research is driven by the increasing frequency and complexity of cyberattacks against global and regional aviation systems, which threaten aviation safety and national sovereignty. Based on data from the International Civil Aviation Organization (ICAO, 2023), cyberattacks in the aviation sector increased by 46% between 2020–2023, while the State Cyber and Cryptography Agency (BSSN, 2023) recorded more than 210 cyber incidents targeting Indonesia's air transportation system. This study uses a qualitative descriptive method, with two main theoretical foundations, namely George C. Edward III's policy implementation theory and Carl von Clausewitz's military strategy theory which is operationalized through SWOT-AHP analysis. The results of the study show that the implementation of cybersecurity policies in Indonesia's aviation sector still faces obstacles in terms of communication, resources, executive disposition, and bureaucratic structure. Factually, only 37% of national airport operators have cyber incident response teams (CSIRTs), while the digital security budget allocation is still below ICAO's recommendation of 2% of the total operational budget. A special finding from this study is the application of the concept of